Consumer perception towards internet health information resources - Khor, Sheng Han; Wong, Sie Lung; Wong, Michelle Hui Ling; Ooi, Jing Chii; Zhang, Xuan Wei; Yang, Cong Ni (IGI Global, 2016)
This research aims to examine consumer perception towards Internet health information resources. Data was collected among 205 respondents by using convenience sampling and was analyzed using descriptive statistics. Descriptively, there was more females' respondent than males' respondent in this survey where all of them are recently undertaking degree courses. The result shows perceived ease of use and perceived usefulness was the main factor that motivates students in using internet health information resources.